Morphological recovery of beach severely damaged by the 2011 great east Japan tsunami. (15th October 2019) - Hoang, Vo Cong; Tanaka, Hitoshi; Mitobe, Yuta
Abstract: The Great East Japan tsunami, which occurred on 11 March 2011 (the 2011 tsunami), caused significant changes to the coastal and estuarine morphology along the Sendai coast, Miyagi prefecture, Japan. The recovery process, which took place subsequently after the tsunami, is investigated using aerial photographs, bathymetry data, and Empirical Orthogonal Function (EOF) method. Results from the aerial photograph analysis indicate that the shoreline was in the dynamic equilibrium condition in the period before the tsunami (Period 1). The recovery of the shoreline was very fast in the period of two years post event (Period 2). However, it was more stable for the period of the next 4.5 years (Period 3). The analysis on the bathymetry data indicates that, besides the sediment supply from adjacent coasts, eroded sediment of the offshore seabed was transported onshore and led to a mass recovery of the shoreline at the lagoon areas. The littoral system of the Sendai coast also changed significantly between the periods before and after the tsunami, as well as between Periods 2 and 3. The sediment deposited inland and in the lagoon areas is perceived as the main reason that caused the retreat inwardly of about 70 m–80 m of the shoreline after the tsunami. Regarding the EOF analysis, the reflected coastal processes of the first three dominant components from the EOF analysis for two shoreline data sets after the tsunami can be explained. In Period 2, the morphological recovery at severely damaged areas (lagoons) was the most dominant process, whilst the second one was the cross-shore variety of shoreline which was the most dominant process preceding tsunami. The contribution rate of the first and second components in Period 2 is about 4 times different. In the period of the next 4.5 years (Period 3), the cross-shore variety of shoreline which was induced by high waves came back to be the most dominant process, whilst the second component reflects the longshore sediment transport. These two dominant components are similar to the ones before the tsunami. The contribution rates of the first two components before and after the tsunami are relatively close as well. That confirms that the coastal processes have returned back to the conditions before the tsunami. This is an important finding which is deduced from this study because a strong tsunami such as the 2011 tsunami could have been a major disturbance, tipping the "normal" cross-, long-shore variability of shoreface water interface towards a different regime.